Representasi Sosial Masyarakat Mesir dalam Novel Yawmu Qutila al-Za'īm Karya Naguib Mahfouz: Analisis Sosiologi Sastra Perspektif Wellek dan Warren - Ahmad Buruji Attariq; Yayan Rahtikawati; Resa Restu Pauji (Dzil Majaz: Journal of Arabic Literature, 2026)
The open-door economic policy (Infitah) during the presidency of Anwar Sadat (1970–1981) triggered a socio-economic crisis with wide-ranging impacts on Egyptian society; however, the representation and critique of this inequality within literary works still requires comprehensive study. This research aims to analyze the social representation of Egyptian society during the Infitah era in the novel Yawmu Qutila al-Za'im by Naguib Mahfouz. Using a qualitative descriptive method with René Wellek and Austin Warren's sociology of literature approach, this study analyzes textual data in the form of quotations, dialogues, and descriptions of events from the digital edition published by the Hindawi Foundation (2022). The results show that the novel represents six interrelated social aspects: (1) economics, marked by rising prices and the burden of living costs that hindered the younger generation's marriage prospects; (2) politics, depicting the assassination of Sadat and the panic it caused throughout society; (3) education, highlighting the phenomenon of educated unemployment and declining trust in formal education; (4) religion, recording the simplification of religious practices and the shift of religious education into the family domain due to economic pressure; (5) culture, portraying the staple food foul medames as a symbol of social solidarity amid the crisis; and (6) social life, presenting intergenerational conflict between life principles and financial reality. This research contributes to reaffirming the novel's function as a critical social document of the Infitah policy while enriching the study of modern Arabic literary sociology.